Religious affiliation and major depressive episode in older adults: a cross-sectional study in six low- and middle- income countries - Julian A. Fernández-Niño; Ietza Bojorquez; Carolina Becerra-Arias; Claudia I. Astudillo-Garcia (BMC, 2019)
Abstract Background The relationship of religious affiliation and mental health is complex, and being part of a minority religious group could have negative effects on mental health. In this study, we assessed the association between religious affiliation and major depressive episode (MDE) in older adults (> = 60 years) from China, Ghana, India, Mexico, Russia and South Africa. Methods We conducted a secondary analysis of data from the Study on global Ageing and adult health (SAGE), with six nationally-representative community-based samples (n = 21,410). Religious affiliation was self-reported by participants, and we defined MDE based on ICD-10 classification. We estimated the association of MDE with religious affiliation versus no religious affiliation, and minority versus majority affiliation. Results We observed no association between having a religious affiliation (vs. no affiliation) and the odds of MDE in older adults. In most cases minorities had higher odds of MDE as compared with the majority religion, but the associations were only significant for Muslims in Ghana and for Muslims, Hindus and Other in South Africa. Conclusions While the results were significant only for two countries, we observed higher odds of MDE among minorities in most of them. Older adults who are members of religious minorities might be at risk for mental health problems, and there is a need for public health interventions aimed at them.